2021
DOI: 10.3389/fonc.2021.757650
|View full text |Cite
|
Sign up to set email alerts
|

Long Non−Coding RNA H19 Regulates Glioma Cell Growth and Metastasis via miR-200a-Mediated CDK6 and ZEB1 Expression

Abstract: Long non-coding RNAs (lncRNAs) serve essential roles on various biological functions. Previous studies have indicated that lncRNAs are involved in the occurrence, growth and infiltration of brain tumors. LncRNA H19 is key regulator in the pathogenesis of gliomas, but the underlying mechanisms of H19-regulated tumor progression remain unknown. Therefore, we investigated the effects and mechanism of action of lncRNA H19 on the homeostasis of glioma cells. As a novel oncogenic factor, up-regulation of H19 was abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The very indication that this H19 affects MET comes through the miRNA it targets as this miRNA is very well known to be involved in regulation of EMT ( 29 ), thus making this miRNA an attractive cancer biomarker ( 30 ). Similar to our findings reported here, H9 was found to regulate EMT marker ZEB1 ( 19 ) which thus appears to be important EMT gene regulated by lncRNAs. Similarly, lncRNA SUMO1P3 also seems to affect EMT as it regulates another EMT biomarker e-cadherin ( 21 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The very indication that this H19 affects MET comes through the miRNA it targets as this miRNA is very well known to be involved in regulation of EMT ( 29 ), thus making this miRNA an attractive cancer biomarker ( 30 ). Similar to our findings reported here, H9 was found to regulate EMT marker ZEB1 ( 19 ) which thus appears to be important EMT gene regulated by lncRNAs. Similarly, lncRNA SUMO1P3 also seems to affect EMT as it regulates another EMT biomarker e-cadherin ( 21 ).…”
Section: Discussionsupporting
confidence: 89%
“…The top six lncRNAs have been proven to exhibit multiple effects against glioma cells. H19 lncRNA has been shown to promote the proliferation, migration and invasion of glioma cells ( 19 ) through targeting of miR-200a. LINC00152 is similarly expressed at higher levels in gliomas where it increases proliferation and invasion ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovaleva [41] also found a variant of the HIF-1A gene C1772T polymorphism, which could be used as a molecular genetic molecule for predicting the risk of IS. CDK6 can activate the transcription of downstream genes involved in cell cycle regulation [42]. Zhao et al [43] found that miR-424 inhibited the proliferation and activation of microglial cells by targeting cell cyclins, such as CDK6 and CDC25A, and exerted neuroprotective effects on the ischemic brain.…”
Section: Plos Onementioning
confidence: 99%
“…Lnc-ATB, a long non-coding RNA, decreased the expression of miR-200c to promote cholangiocarcinoma (CCA) growth [ 47 ]. Lnc RNA H19 targeted miR-200a and promoted the invasion and migration of glioma cells [ 48 ].…”
Section: Regulation Of Mir-200 Family Expressionmentioning
confidence: 99%